The Barriers in the Implementation of Antimicrobial Stewardship Programs - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2021)
The resistance to antimicrobial is considered one of the most important risks that affect public health and health care. Antimicrobial stewardship programs (ASPs) contain a series of interventions that decrease the inappropriate use of antimicrobials. There are many barriers to the implementation of ASPs. To improve the use of antibiotics, it is important to overcome these barriers. In the present study, we searched for articles about the barriers of implementing ASPs using the keyword â€œASPsâ€ in the PubMed database. The present study found that the most common hurdles are lack of training, knowledge, interprofessional conflict, interspecialty conflict, and lack of resources.